PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN UNTUK MEMBANGUN MINAT BERKUNJUNG KEMBALI : STUDI PADA HOTEL X KOTA PEKALONGAN - Tri Waluyo (Universitas Nasional, 2020)
Pekalongan City entered the creative city network UNISCO in Crafts & Folk Art category in December 2014 and has City branding World's city of Batik. Pekalongan is not only batik, but there are religious and nature tourism. With so many tours, infrastructure is needed for lodging, both villa and hotel, which will become a business opportunity for hotel entrepreneurs. The condition is interesting to be studied, with the aim to analyze how the relationship influence between image, service quality, to customer satisfaction and interest visiting again. The independent variable used in this research is data from Image, service quality. And for customer satisfaction, interest returns as a dependent variable. As a representation of this research sample is hotel company X located in Pekalongan city. Tests were conducted between the two independent variables against the two dependent variables. The sampling technique used is purposive sampling. The type of research data is primary data. The results show that both independent variables have a positive and significant effect on customer satisfaction, and there is a positive influence on the interest of visiting again.